Research progress of extracellular vesicles and exosomes derived from mesenchymal stem cells in the treatment of oxidative stress-related diseases - Zhang, Wenwen; Wang, Tingyu; Xue, Yuanye; Zhan, Bingbing; Lai, Zengjie; Huang, Wenjie; Peng, Xinsheng; Zhou, Yanfang (Frontiers in Immunology, 2023)
There is growing evidence that mesenchymal stem cell-derived extracellular vesicles and exosomes can significantly improve the curative effect of oxidative stress-related diseases. Mesenchymal stem cell extracellular vesicles and exosomes (MSC-EVs and MSC-Exos) are rich in bioactive molecules and have many biological regulatory functions. In this review, we describe how MSC-EVs and MSC-Exos reduce the related markers of oxidative stress and inflammation in various systemic diseases, and the molecular mechanism of MSC-EVs and MSC-Exos in treating apoptosis and vascular injury induced by oxidative stress. The results of a large number of experimental studies have shown that both local and systemic administration can effectively inhibit the oxidative stress response in diseases and promote the survival and regeneration of damaged parenchymal cells. The mRNA and miRNAs in MSC-EVs and MSC-Exos are the most important bioactive molecules in disease treatment, which can inhibit the apoptosis, necrosis and oxidative stress of lung, heart, kidney, liver, bone, skin and other cells, and promote their survive and regenerate.